Dinamika Persaingan Usaha Tidak Sehat Dalam Industri Minyak Goreng: Studi Kasus Putusan KPPU No. 15/KPPU-I/2022 - Rahman, Naila Kamila; Elvira, Olga; Santika, Syahirah Rafah; Tarina, Dwi Desi Yayi (Media Hukum Indonesia (MHI), 2025)
Cartel practices are one of the business competition issues that disturb the public and can harm both producers and consumers because these practices fall under trade monopoly or unfair business competition. The Business Competition Supervisory Commission (KPPU) plays a role in enforcing the rules contained in Law Number 5 of 1999 concerning the Prohibition of Monopolistic Practices and Unfair Business Competition. This research is normative in nature, focusing on how regulations and law enforcement address cartel practices in Indonesia through a statutory approach and a case approach.